Influence of Work Motivation, Occupational Health and Safety on Employee Performance of PT. Cipta Abadi Jaya Trans with Job Satisfaction as Mediating Variable - Farley Dharmawan; Deden Kurniawan (Journal of Accounting and Finance Management, 2023)
Basically, this study aims to examine and analyze the importance of work motivation and occupational health and safety on employee performance by using job satisfaction variable as a mediating variable in the PT. Cipta Abadi Jaya Trans. By using a quantitative research design with an explanatory survey method, namely data collection using a questionnaire with a Likert scale model. The sample collection of organic employee respondent data is 130 respondents. Structural Equation Modeling (SEM) PLS Version 3.2.9 is used as a tool to process data. In this study using four variables, thirteen dimensions and fourty three indicators. From the results of this study it can be concluded that all variables have a significant effect on employee performance, namely: 1) Work motivation on employee performance. 2) Occupational health and safety on employee performance, 3) Job satisfaction on employee performance, 4) Work motivation on job satisfaction, 5) Occupational health and safety on employee performance, 6) Job satisfaction mediates the effect of work motivation on employee performance, 7) Job satisfaction mediates the effect of occupational health and safety on employee performance.